Locks - Barnes, Stephen (Department of English Language and Literature, 2016)
LOCKS is the story of a young woman trying to take authorship of her life. Hers is one of three story·strands that interweave, each protagonist vying for personal significance within that plait. L's sphere of experience is contained within the room she has grown-up in, her only companion an elderly woman, Marmalade, who has educated her through the allegories of fairy tales. Unaware of an accessible outside world, all references to a world beyond her experience are relegated to the fairytale mythology of knights and slavering wolves.